Fast distributed algorithms to make mutually coordinated decisions in stringent real time - Stetsyura, G. G. (Automation and remote control, 2008)
Algorithms for fast detection and elimination of false results of computations in the stringent real-time multiprocessor and multicomputer systems based on combined calculation and data transmission were proposed.